2017
DOI: 10.5942/jawwa.2017.109.0116
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Microbial Signatures From Advanced Treated Wastewater Biofilms

Abstract: Next‐generation sequencing (NGS) and metagenomics were used to identify microbial communities in biofilms of microfiltration (MF) and reverse osmosis (RO) membranes in an advanced water purification facility (AWPF) that treats municipal wastewater to produce potable quality water. Secondary treated wastewater effluent is the source of influent to the AWPF treatment train and was also characterized by NGS. Results show low bacterial diversity in biofilms obtained from the feed‐side surfaces of MF and RO membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 32 publications
3
22
0
Order By: Relevance
“…These authors noted that the system was so effective in the removal of microorganisms that they were unable to produce enough quantities of DNA for metagenomic sequencing even with large volumes of sampled water which was the original goal of their study. The findings from this study and other studies from OCWD AWPE [2,10,12,13] showed that advance waste water treatment has the potential to reduce microbial contaminants to undetectable levels.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…These authors noted that the system was so effective in the removal of microorganisms that they were unable to produce enough quantities of DNA for metagenomic sequencing even with large volumes of sampled water which was the original goal of their study. The findings from this study and other studies from OCWD AWPE [2,10,12,13] showed that advance waste water treatment has the potential to reduce microbial contaminants to undetectable levels.…”
Section: Introductionsupporting
confidence: 67%
“…For instance, in some of the most advanced water treatment systems, undisinfected influent or secondary treated municipal wastewater may go through the purification process from microfiltration (MF), reverse osmosis (RO), and UV light. In some processes H 2 O 2 is added before UV treatment as well as lime to further stabilize the purified water [2]. In most cases, these processes may reduce microbial population to an undetectable level, and at this point the water is ready to be acceptable for numerous applications, from irrigation and industrial processing to domestic water supply [3].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the field of metagenomics has developed rapidly and effectively obviates the need to isolate and culture microorganisms by utilizing the genetic material of a sample to identify accurately the functional gene composition [12,13]. That major accomplishment has allowed in depth comparison and exploration of microbial ecology [14,15], including the metabolic profile of complex microbial ecosystems [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Metagenomic DNA from microbial communities of each sample was harvested by centrifugation and ultrafiltration and then sequenced via whole genome shotgun sequencing protocols to provide an accurate identification as well as functional capability of microbial communities (Leddy et al, 2017). In shotgun Journal of Geoscience and Environment Protection sequencing, random fragments of carefully prepared genomic libraries are sequenced with overlapping ends; which are then aligned into whole genomic reads using a rapid identification platform to detect and quantify all microbes including bacteria, archaea, viruses, fungi and protozoa in any sample in one step (Venter et al, 2004).…”
Section: Microbiological Analysismentioning
confidence: 99%
“…Advances in the analysis of metagenomes have allowed environmental microbiologists to simultaneously identify microorganisms and compute their relative abundance in a biofilm (Hwang et al, 2012). In multi-domain communities, whole genome shotgun sequencing protocols and analysis allow the detection and quantification of target genes and all DNA-based life forms of various domains-bacteria, algae, fungi, protozoans and viruses in biofilms, as described in Leddy et al (2017). Characterization of community fingerprints in biofilms can establish system benchmarks and provide information on how to improve performance and control fouling.…”
Section: Introductionmentioning
confidence: 99%